Model of knowledge management to improve the quality of scientific research in universities in Peru - Zeña Quépuy, Carlos Natalio (2016)
The present work arose after the situational diagnosis and observation of thesis quality and Scientific articles produced in Pre and Postgraduate in Universities of the country. We worked with a representative sample of 50 university actors, who answered the questionnaire and scientifically allowed to verify the problematic situation. A model of knowledge management based on pedagogical constructivism, curriculum by competences in universities of the country and in strategic management was proposed. This model constitutes a multidisciplinary educational effort, aimed at changing attitudes, values, behaviors and structure of scientific research, adapted with new conjunctures, technologies and challenges in the university.